PKK Membership Participation in the Sustainable Development: Analysis of Arnstein's Participation Levels - Nurfadillah; Daeva Mubarika Raisa; Putra Astaman; Megawati; Fadilah Nurdin (FAKULTAS PERTANIAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2025)
KUB Anggrek is a joint business group formed as a result of an initiative by the PKK, which promotes creative economic crafts based on local potential, namely banana leaves. This KUB is located in Aska Village, South Sinjai District, Sinjai Regency. When it was first formed, KUB Anggrek was very active in production, participated in national exhibitions, and served as instructors for other districts. However, over time, this KUB experienced a decline in membership, business stagnation, and even a vacuum. This study aims to describe the level of participation of PKK members in Aska Village in the activities and programs of KUB Anggrek and their role in the development of this business group. The method used is a descriptive qualitative approach with a case study design. Data collection techniques include in-depth interviews, observation, and documentation study. Informants were determined using purposive sampling, while data analysis was conducted interactively, which includes data reduction, data presentation, and conclusion drawing and verification. The results of the study show that the level of PKK member participation is at the “informing,” “consultation,” “placation,” and “partnership” levels. However, it has not yet reached the level of “delegated power” and “citizen control.” The roles of PKK members in KUB Anggrek include information recipients, training participants, technical implementers, and coordinators, but they do not yet have full control over strategic decisions or business management.